1974
DOI: 10.1136/jnnp.37.5.502
|View full text |Cite
|
Sign up to set email alerts
|

Nodal gap substance in diabetic nerve

Abstract: SYNOPSIS Anoxia and KCI have been used to inactivate peripheral nerves by depolarization conduction block. Investigation of the inactivation patterns in isolated sciatic nerves of healthy and alloxan-diabetic rats suggests that the paranodal gap substance of healthy nerve behaves as an effective periaxonal diffusion barrier. In diabetic nerve the permeability of this barrier is significantly increased. A marked reduction in the K' binding capacity of the nodal gap substance has been demonstrated in myelinated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…K v 1-channels are clustered at the juxtaparanodal regions and along the internodes of myelinated peripheral axons (Salzer, 2003). It was previously observed that paranodal/juxtaparanodal potassium binding sites are reduced in nerves from diabetic patients (Seneviratne and Weerasuriya, 1974). We have specifically shown that the K v 1.2 distribution is altered in both db/db mice and in T2DM nerve biopsies thus providing, to our knowledge, the first direct demonstration of such an alteration in axonal ion channels in diabetic patients.…”
Section: Discussionmentioning
confidence: 59%
“…K v 1-channels are clustered at the juxtaparanodal regions and along the internodes of myelinated peripheral axons (Salzer, 2003). It was previously observed that paranodal/juxtaparanodal potassium binding sites are reduced in nerves from diabetic patients (Seneviratne and Weerasuriya, 1974). We have specifically shown that the K v 1.2 distribution is altered in both db/db mice and in T2DM nerve biopsies thus providing, to our knowledge, the first direct demonstration of such an alteration in axonal ion channels in diabetic patients.…”
Section: Discussionmentioning
confidence: 59%
“…Another functional abnormality of diabetic nerves, namely the increased resistance to anoxic inactivation -the Steiness' phenomenon -which also occurs in alloxan diabetic rats may possibly be associated with the node changes demonstrated here [12,13]. Two main types of nerve fibre degeneration are generally recognized, axonal degeneration and segmental demyelination, diphtheritic neuropathy being the archetype of the latter.…”
Section: Discussionmentioning
confidence: 74%
“…Seneviratne and Weerasuriya (1974) showed altered cation binding in the nodal gap of myelinated nerve fibers of alloxan-diabetes rats, whereas Sharma and Thomas (1974) did not find any changes of nodal gap by cytochemical analysis. Intramembranous particles of globular proteins are reported to be intimately related to Na-K ATPase activity (Deguchi et al 1977) which mainly locates in the nodal gap and was demonstrated to decrease in the sciatic nerves of streptozotocin-diabetes rats (Das et al 1976).…”
Section: Discussionmentioning
confidence: 99%